The Potential of Organic and Inorganic Nutrient Sources in Sub-Saharan African Crop Farming Systems - Ngetich, Felix K.; Shisanya, Chris A.; Mugwe, Jayne; Mucheru-Muna, Monicah; Mugendi, Daniel (IntechOpen, 2012)
None